Finite element analysis of restoring length with multiple internal fixations in calcaneal body fracture - Xiang Yao; Peiqi Ding; Chong Wang; Han Miao; Yicong Chao; Jiawei Wang; Minjie Hu; Jilei Tang (Scientific Reports)
Abstract Calcaneal body fractures are often associated with varying degrees of shortening deformities. Restoring calcaneal length is crucial for the functional prognosis of the foot. Through finite element analysis, this study compared the biomechanical effects of multiple fixation schemes for calcaneal fractures. We delineated and assembled the finite element model of the Sanders type II calcaneal fracture and four internal fixation simulations (namely distraction screw, lag screw, frame locking plate, and T-shaped locking plate). Different axial forces (350, 700, and 1400 N) were then applied to simulate various postures. We then compared the inner and outer shortening distances (D1 and D2, respectively), equivalent von Mises stress, and maximum von Mises stress of the calcaneus. In the individual model, with an increase in the pressure, D1, D2, and the maximum von Mises stress gradually increased. At 1400 N, D1 and D2 for the internal fixation schemes were as follows: distraction screw (0.03 mm, 0.1 mm) < T-shaped locking plate (0.45 mm, 0.26 mm) < frame locking plate (0.50 mm, 0.26 mm) < lag screw (0.66 mm, 0.64 mm). The maximum von Mises stress values for the internal fixation methods were as follows: lag screw (491.0 MPa) < distraction screw (663.1 MPa) < frame locking plate (772.7 MPa) < T-shaped locking plate (931.8 MPa). In patients with calcaneal body fractures, the distraction screw is a potential therapeutic option for resisting calcaneal shortening.